Skin Biophysical Parameters and Patch Test Results in People Predisposing to Xiaotong Tiegao Induced Irritant Contact Dermatitis. (24th February 2019) - Cheng, Hai-yan; Li, Lin-feng
Abstract : Background . Xiaotong Tiegao (XTT) is an ancient topical Tibetan medicine plaster which is widely used in China. Irritant contact dermatitis (ICD) caused by XTT is very common. It is still unclear why some people are more prone to develop ICD. The aim of this study is to study the baseline skin biophysical parameters and patch test results in individuals predisposing to XTT induced ICD. Methods . During a four-month period, 149 healthy volunteers with ICD and 50 volunteers without ICD after applying XTT were recruited. The skin biophysical parameters were measured, and contact allergy to 20 common allergens was patch tested, at two weeks after the ICD was recovered. Results . There were no significant differences in age and sex between ICD and control groups. It was found that skin median melanin value (176.50 vs 189.50, P < 0.05, Mann-Whitney U-test) and erythema value (319.90 ± 70.49 vs 347.93 ± 84.55, P < 0.05, Independent-Samples T test) were much lower in ICD than control group. Overall patch test results were not different, but the positivity rate of nickel sulfate (15.44% vs 4.00%, P < 0.05, Fisher's exact test) was significantly higher in ICD group. Conclusions . In conclusion, people with nickel allergy, lower values of skin melanin, and erythema are predisposing to develop ICD.